O jogo de empresas baseado no custeio ABC JogABC - Rossato, Roger Rabenschlag (2006)
The business game, called JogABC, elaborated in this study shows to the players how the ABC functions. This method of costing, for having high implantation costs, is rare, being restricted only for the companies which the costs of this implantation are smaller than the benefits that they provides. For the mathematical modeling of the game the Microsoft Excel 97 was used. The JogABC simulate the interaction between a first company who will have as many branch offices as were the participant teams, being these operations in the branch of clothes, producing shirts, dresses and pants. The Game uses a production refereed for the first company, that decides the bulk of production and the prices that will be paid for this products, this form, the branch offices will use this earns to buy the improvements that will be applied in its respective productive processes in order to improvement the activities, will be the winner the team that in the end of the game to possess the minor production cost. The JogABC shows to the players as a company who uses the ABC can know accurately where its productive process can be improved, besides evidencing the main difference of this costing for those distribute indirect costs attributed to the products using a less arbitrary form. Adding it the knowledge on the ABC costing that the JogABC propitiates, also can be cited the improvement of the abilities as group behavior who involve the interpersonal relationship that a work in team demands and that it is strong present in the method of business game. The game can be used in disciplines of graduation, after-graduation and professional.